Job Satisfaction, Mental Well-Being, Motivations, and Challenges of Selected Migrant Filipino Teachers Working in the United States of America - Presquito, Rhey Mark; Madrigal, Dennis V. (Technium Social Sciences Journal, 2025)
The study investigated the complex interplay of job satisfaction, mental well-being, and motivating factors among migrant Filipino teachers in the United States during the 2024-2025 school year, aiming to inform a proposed induction program. Employing a multimethod research design, the study found that while salary significantly influenced job satisfaction and overall well-being, there was no direct correlation and well-being. Qualitative insights revealed a deeply motivating journey driven by financial stability, professional growth and better compensation. However, the challenges included student behavior differences, adjusting to new education system, resource scarcity, and lack of parental involvement despite these hurdles, teachers demonstrated remarkable resilience and commitment. The findings offer valuable baseline data for school districts and policymakers to develop targeted supported system, improve retention, and foster a more inclusive environment for migrant Filipino teachers, ultimately enriching the broader education community.